Geographic distribution of human Blastocystis subtypes in South America (2016)
Blastocystis is a cosmopolitan enteric protist colonizing probably more than 1 billion people. This protozoan exhibits genetic diversity and is subdivided into subtypes (STs). The aim of this study was to determine the distribution of Blastocystis STs in symptomatic and asymptomatic human samples from different countries of South America. A total of 346 fecal samples were genotyped by SSU rDNA showing ST1 (28.3%), ST2 (22.2%), ST3 (36.7%), ST4 (2%), ST5 (2.3%), ST6 (2%), ST7 (2.3%), ST8 (0.6%), ST12 (0.9%) and a novel ST (2.7%). These findings update the epidemiology of Blastocystis in South America and expand our knowledge of the phylogeographic differences exhibited by this stramenopile. © 2016 Elsevier B.V.